MISI KRISTEN DAN DAMPAKNYA BAGI KEMAJEMUKAN: PANDANGAN IPTH. BALEWIYATA MALANG - Syaiful Arif (Harmoni, 2014)
As a school of theology under the auspices of the East Java Christian Church (GKJW), the Theological Education Institute (IPTh.) of Balewiyata, Malang has developed a substantive understanding of Christian missionizing. This understanding froms the basis of the moderate theology held by GKJW and the Christian community of East Java. This concept of moderate missionizing sees missions as a proclamation and a testimony for the truth of Christ’s teaching. It is a practice of theological tenets in the shape of religious tolerance and the caring of humanity. Interestingly, the moderate mission has facilitated the indigenization of Christianity in Java, leading to the formation of a unique “Javanese Christian” culture.